2018
DOI: 10.3390/en11102644
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing of a Photovoltaic/Wind/Biogas/Pumped-Hydro Off-Grid Hybrid System for Rural Electrification in Sub-Saharan Africa—Case Study of Djoundé in Northern Cameroon

Abstract: Traditional electrification methods, including grid extension and stand-alone diesel generators, have shown limitations to sustainability in the face of rural electrification challenges in sub-Saharan Africa (SSA), where electrification rates remain the lowest in the world. This study aims at performing a techno-economic analysis and optimization of a pumped-hydro energy storage based 100%-renewable off-grid hybrid energy system for the electrification of Djoundé, which is a small village in northern Cameroon.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(56 citation statements)
references
References 43 publications
1
55
0
Order By: Relevance
“…In addition, it allows the user to conduct sensitivity analyses for further assessment. Due to the various functions of HOMER with customized options, many studies have used it as a tool for conducting techno-economic feasibility analyses of off-grid energy systems [3,[6][7][8]11,[23][24][25]. Due to the various functions within HOMER with customized options, this study also uses HOMER to derive the NPC and LCOE of the most effective off-grid energy system for the selected location.…”
Section: Homer Simulation For An Off-grid Systemmentioning
confidence: 99%
“…In addition, it allows the user to conduct sensitivity analyses for further assessment. Due to the various functions of HOMER with customized options, many studies have used it as a tool for conducting techno-economic feasibility analyses of off-grid energy systems [3,[6][7][8]11,[23][24][25]. Due to the various functions within HOMER with customized options, this study also uses HOMER to derive the NPC and LCOE of the most effective off-grid energy system for the selected location.…”
Section: Homer Simulation For An Off-grid Systemmentioning
confidence: 99%
“…The only selection criterion was the availability of data from the NASA database. The selected locations are listed as follows: Banyo (1), Garoua (2), Maroua (3), Meiganga (4), Mokolo (5), Mora (6), Ngaoundéré (7), Poli (8), Tcholoré (9), Tibati (10), Tignère (11), and Yagoua (12).…”
Section: The Area Of the Study And Selected Alternative Sitesmentioning
confidence: 99%
“…If the NPV were considered as the only criterion of evaluation, Mora would be the best site, followed by Mokolo and Poli. The electricity fed into the grid, the reduction of greenhouse gas emissions, and the capacity factor of the PV system all vary from Banyo to Mora, from 10,671 MWh/year to 11,567 MWh/year, from 9156 tCO 2 /year to 9797 tCO 2 /year, and from 24.4% to 26.1%, respectively. All sites meet the NPV constraint (NPV ≥ 0€).…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In Zambia, Shane and Gheewala [50] estimate about 1.473 × 10 9 m 3 biogas from animal dung and 1.819 × 10 9 m 3 from crop residues. A study in Cameroon showed good prospects for biogas use as fuel for rural electrification, in a hybrid configuration combining biogas with photovoltaic, wind and pumped hydro [51]. Studies on biogas potential have been done in several other African countries.…”
Section: Overview Of Large Biogas Systems In Africamentioning
confidence: 99%